Neutrophilia in locally advanced cervical cancer: A novel biomarker for image-guided adaptive brachytherapy? - Escande, Alexandre (Oncotarget, 2016)
OBJECTIVE: To study the prognostic value of leucocyte disorders in a prospective cohort of cervical cancer patients receiving definitive chemoradiation plus image—guided adaptive brachytherapy (IGABT). RESULTS: 113 patients were identified. All patients received a pelvic irradiation concomitant with chemotherapy, extended to the para-aortic area in 13 patients with IVB disease. Neutrophilia and leukocytosis were significant univariate prognostic factors for poorer local failure-free survival (p = 0.000 and p = 0.002, respectively), associated with tumor size, high-risk clinical target volume (HR-CTV) and anemia. No effect was shown for distant metastases but leukocytosis and neutrophila were both poor prognostic factors for in-field relapses (p = 0.003 and p < 0.001). In multivariate analysis, HR-CTV volume (p = 0.026) and neutrophils count > 7,500/μl (p = 0.018) were independent factors for poorer survival without local failure, with hazard ratio (HR) of 3.1. MATERIALS AND METHODS: We examined patients treated in our Institution between April 2009 and July 2015 by concurrent chemoradiation (45 Gy in 25 fractions +/− lymph node boosts) followed by a magnetic resonance imaging (MRI)-guided adaptive pulse-dose rate brachytherapy (15 Gy to the intermediate-risk clinical target volume). The prognostic value of pretreatment leucocyte disorders was examined. Leukocytosis and neutrophilia were defined as a leukocyte count or a neutrophils count exceeding 10,000 and 7,500/μl, respectively. CONCLUSIONS: Neutrophilia is a significant prognostic factor for local relapse in locally advanced cervical cancer treated with MRI-based IGABT. This biomarker could help identifying patients with higher risk of local relapse and requiring dose escalation.